2008
DOI: 10.1002/eat.20527
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of eating disorders in women with facial hirsutism: An epidemiological cohort study

Abstract: Our study demonstrates that hirsute women are at high risk of developing an eating disorder. Factors associated with eating disorders are examined and explanatory hypotheses are suggested for the possible underlying mechanisms in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
(17 reference statements)
0
38
0
2
Order By: Relevance
“…23,25,29,39,40 The participants with higher scores on the PHQ-9 and its 2 subscales reported lower self-esteem, higher mental health service use, and more physical illnesses, indicating good concurrent validity. Previous studies have also reported that an increase in the severity of depression was associated with negative self-esteem, [40][41][42] more physical illnesses, 43,44 and higher mental health service use. [43][44][45] In the current study, the AUC for MDD was 0.90 for the PHQ-9 and 0.87 for the PHQ-2, which are comparable to those in previous studies on adolescents in primary care.…”
Section: Discussionmentioning
confidence: 80%
“…23,25,29,39,40 The participants with higher scores on the PHQ-9 and its 2 subscales reported lower self-esteem, higher mental health service use, and more physical illnesses, indicating good concurrent validity. Previous studies have also reported that an increase in the severity of depression was associated with negative self-esteem, [40][41][42] more physical illnesses, 43,44 and higher mental health service use. [43][44][45] In the current study, the AUC for MDD was 0.90 for the PHQ-9 and 0.87 for the PHQ-2, which are comparable to those in previous studies on adolescents in primary care.…”
Section: Discussionmentioning
confidence: 80%
“…Studies of anxiety and PCOS are limited, on the basis of a Medline-PubMed-PsycINFO literature search (e.g., references [9][10][11][12][13][14]. Even though anxiety and depression often coexist, most of the past research on mood in PCOS is limited to prevalence of depression (e.g., references 15,16) with few data on prevalence and severity of anxiety or severity of depression (14).…”
mentioning
confidence: 98%
“…Ghrelin and cholecystokinin secretion following meals are impaired in PCOS, suggesting changed appetite regulation [75,76]. The prevalence of eating disorders was 36% in women presenting with hirsutism [77], and conversely, PCOS was overrepresented in bulimic women [78]. The main study outcome of previous studies was to establish differences in calorie intake and diet composition between patients with PCOS and controls and differences in the intake of vitamin D-rich food substances was not especially mentioned.…”
Section: Vitamin D Levels In Pcosmentioning
confidence: 97%